The associations of daily steps and body mass index with incident gastroesophageal reflux disease in older adults - Saavedra, Joey M.; Lefferts, Elizabeth C.; Song, Bong Kil; Lee, Duck-chul (Frontiers in Sports and Active Living, 2024)
Background High body mass index (BMI) is a major risk factor of gastroesophageal reflux disease (GERD), a prevalent morbidity of older adulthood linked to lower quality of life and an increased risk of esophageal cancers. Daily stepping behavior, the most common physical activity of older adulthood, is associated with an array of favorable health outcomes, sometimes independent of high BMI. Whether stepping behavior is associated with the incidence of GERD independently or in combination with BMI is currently unclear. Materials and methods We followed 442 individuals (58.4% female) aged 65–91 years enrolled in the Physical Activity and Aging Study. Baseline steps were obtained by pedometer and categorized by tertiles (lower, middle, upper), while BMI was categorized into normal weight, overweight, and obesity. To explore joint associations, daily steps were dichotomized into “high steps” (middle/upper tertiles) and “low steps” (lower tertile), while BMI was dichotomized into normal weight and overweight/obesity. The joint exposure categories included “low steps and overweight/obesity,” “low steps and normal weight,” “high steps and overweight/obesity,” and “high steps and normal weight.” Results We identified 35 (7.9%) cases of GERD over a mean follow-up of 2.5 years. Compared to the lower tertile of steps, the hazard ratios (HRs) [95% confidence intervals (95% CIs)] of GERD were 0.44 (0.20–0.96) and 0.17 (0.05–0.54) for the middle and upper tertiles, respectively, after adjusting for confounders (including BMI). Compared to normal weight, the HRs (95% CIs) of GERD were 1.35 (0.54–3.37) and 3.00 (1.19–7.55) for overweight and obesity, respectively, after adjusting for confounders (including steps). In a joint analysis, compared to “low steps and overweight/obesity,” the HRs (95% CIs) of GERD were 0.32 (0.10–1.00), 0.23 (0.10–0.54), and 0.20 (0.07–0.58) for “low steps and normal weight,” “high steps and overweight/obesity,” and “high steps and normal weight,” respectively. Conclusion Higher daily steps were associated with a lower risk of GERD in older adults, independent of BMI. Since accumulating steps through walking is an achievable and acceptable modality of physical activity in older adulthood, future lifestyle interventions designed to achieve high daily steps counts may have favorable implications for the development of GERD in older adults of any BMI status.